Pedagogical Support and Skills Development for Novice Teachers of Public Secondary School of Garoua Town (Cameroon) - Charles Tchouata Foudjio; Nestor Moutmassou (Researchparks Publishing, 2022)
Teacher at the beginning of their professional careers are usually confronted with new demands that are different from those of the training. They are in general obliged to develop throughout their careers in order to adapt to contextual changes such as school reforms and social change. This professional development is essential for the development of a professional identity and better integration of young teachers. The objective of this study is to show that the development of the skills of novice teachers of public secondary school of Garoua town is determined by the quality of pedagogical support. Thus, the hypothesis that serves as guideline for this work stipulates that pedagogical support improves the development of novice teachers' skills. This hypothesis was verified on the basis of data collected through a questionnaire administered to 148 novice teachers of public secondary school of Garoua town. The results obtained are in favour of a validation of the initial hypothesis. There is therefore a significant and positive correlation between pedagogical support and the development of the skills of novice teachers of public secondary school of Garoua town. In order to better understand the skills deficit observed among novice teachers, semi-directive interviews were conducted with 13 teachers and pedagogical inspectors.